Analysis of Competitive Strategies in Retaining Customers (Study on Makecents Coffee Space in New Terrain) - Syafina, Ashifa Ridza; Nursanjaya, Nursanjaya; Iryani, Lisa; Sukmawati, Cut; Ritonga, Nursakinah (LPPM UIKA Bogor, 2024)
With the increasing popularity of the coffee shop business in the city of Medan, Makecents Coffee Space must implement appropriate competitive and marketing strategies in order to continue to win the competition, attract customers and maintain customer loyalty. witnessing it directly or indirectly is like giving a list of questions to be answered. From the results of the SWOT analysis and discussion, the factors that are the advantages of Makecents coffee space which can be used to increase competitiveness in facing competition between similar businesses are the price and quality factors offered. The strategies carried out by Makecents Coffee Space first analyze what the market wants, then provide a good service process so that it can attract customers, provide attractive product offers, and free customers to comment and provide input by providing stalls for commenting so that they can retain existing customers. already exists and is able to attract more customers. Based on the competitive strategy that has been created, the right strategy for Makecents Coffee Space to retain customers is to pay attention to customer orientation, personalize the customer experience, beautify existing customers by providing stalls so that customers are free to comment so as not to make customers disappointed and result in a decrease in the good value of Makecents. . coffee room. Of the existing strategies, all of them are the core of a market strategy where the company increases its sales of available products and markets through more aggressive marketing efforts.